Developmental origins of osteoporosis: the role of maternal nutrition. - Cooper, C; Harvey, N; Cole, Z; Hanson, M; Dennison, E (2009)
Osteoporosis is a major cause of morbidity and mortality through its association with age-related fractures. Although most effort in fracture prevention has been directed at retarding the rate of age-related bone loss, and reducing the frequency and severity of trauma among elderly people, evidence is growing that peak bone mass is an important contributor to bone strength during later life. The normal patterns of skeletal growth have been well characterised in cross-sectional and longitudinal studies. It has been confirmed that boys have higher bone mineral content, but not volumetric bone density, than girls. Furthermore, there is a dissociation between the peak velocities for height gain and bone mineral accrual in both genders. Puberty is the period during which volumetric density appears to increase in both axial and appendicular sites. Many factors influence the accumulation of bone mineral during childhood and adolescence, including heredity, gender, diet, physical activity, endocrine status, and sporadic risk factors such as cigarette smoking. In addition to these modifiable factors during childhood, evidence has also accrued that fracture risk might be programmed during intrauterine life. Epidemiological studies have demonstrated a relationship between birthweight, weight in infancy, and adult bone mass. This appears to be mediated through modulation of the set-point for basal activity of pituitary-dependent endocrine systems such as the hypothalamic-pituitary-adrenal (HPA) and growth hormone/insulin-like growth factor-1 (GH/IGF-1) axes. Maternal smoking, diet (particularly vitamin D deficiency) and physical activity also appear to modulate bone mineral acquisition during intrauterine life; furthermore, both low birth size and poor childhood growth, are directly linked to the later risk of hip fracture. The optimisation of maternal nutrition and intrauterine growth should also be included within preventive strategies against osteoporotic fracture, albeit for future generations.